+0  
 
+2
62
4
avatar+708 

i think its the one i have selected

 Feb 22, 2019
 #1
avatar
0

ur correct

 Feb 22, 2019
 #2
avatar+708 
+1

can you exaplin why just so i can make sure i understand

jjennylove  Feb 22, 2019
 #3
avatar+98130 
+4

Note that f(-3)  =  -(-3)^2 + 4  =  -(9) + 4  = -5

This is not equal to g(-3)  = 1

 

So...it appears that since -5 < 1  then

 

f(-3) < g(-3)

 

 

cool cool cool

 Feb 22, 2019
 #4
avatar+708 
+1

Thank you! your explaintations really help

jjennylove  Feb 22, 2019

12 Online Users

avatar
avatar